The Influence of Career Development and Work Enthusiasm on The Performance of Employees of the Terminal Service unit type A Karya Jaya Palembang - Anita; Roswaty; Siti Komariah Hildayanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Career development shows a person's emotional and mental reactions to his work, career development affects the quality and quantity in the terminal service unit type a karya jaya Palembang. This study aims to analyse the effect of career development and work enthusiasm on employee performance at the Karya Jaya Palembang Type A Terminal Service Unit. The object of this research is 42 employees of Terminal Service Unit Type A Karya Jaya Palembang. The analysis technique used in this research is multiple linear analysis which is processed using the help of the Statistical Product and Service Solution (SPSS) computer program version 26. Based on the results and discussion, there is an influence of career development and work enthusiasm on employee performance. Career development and work enthusiasm simultaneously have a significant effect on performance variables. From the results of the study it can be concluded that the influence of career development and work enthusiasm has a positive and significant effect on performance on the performance of employees of the terminal service unit type A Karya Jaya Palembang